(untitled) (Journal of Oriental Studies, 2019)
The Arab East region remained a crossroads of important political and economic processes in the second half of the ХХ century. After the II World War in this part of the world, the United States sought to create a militarypolitical bloc aimed to protect its foreign interests. In particular, the United States tried to pursue a clear policy to strengthen its position in Egypt. The fact that Egypt has an effective geopolitical situation, huge human and natural resources and military potential makes it an important participant in international relations. Transforming the Arab East with its “vital interests” the United States plays an important role in Egypt’s foreign policy. Ensuring stability and security in the region was considered as one of the key factors in relation between the two countries. If the US has a leading role in the Middle East, then Egypt as a regional leader has seriously influenced the economic and political development of Arab countries. At that time, Egypt was considered one of the most developed countries in the economic and military relations in the Middle East, such as Iran, Israel and Turkey. Key words: Egypt, USA, cooperation, international relationships, military assistance, economic assistance.